The cost of gold: Mercury contamination of fishes in a Neotropical river food web - Montaña,Carmen G. (2021)
Abstract In South America, mercury contamination due to gold mining operations is a threat to both biodiversity and human health. We examined mercury (Hg) concentrations in fishes that constitute important subsistence fisheries from mined and non-mined tributaries in the middle Mazaruni River, Guyana. Mercury concentrations and trophic food web structure (based on carbon and nitrogen stable isotopes) were characterized for primary basal sources and 39 fish species representing seven trophic guilds. Fishes collected at mined sites had higher mercury concentrations; piscivores and carnivores had the highest Hg concentrations and exhibited significant Hg biomagnification. Our results showed that medium- to large-bodied fishes commonly eaten by local people contained Hg values that exceed the World Health Organization (WHO) criteria, and pose a health concern for riverine communities along the Mazaruni River that depend on fish as their main source of protein. Further research to determine the sources of Hg contamination and how it affects human health in this neotropical river must become a top priority. In addition, more research on how Hg contamination impacts the fishes themselves and overall aquatic biodiversity is also needed in the Mazaruni River which has both high fish endemism and diversity.